Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 30 May 2017, 06:16

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Function F(x) satisfies F(x) = F(x^2) for all of x. Which

 post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
CEO
Joined: 21 Jan 2007
Posts: 2740
Location: New York City
Followers: 11

Kudos [?]: 943 [0], given: 4

Function F(x) satisfies F(x) = F(x^2) for all of x. Which [#permalink]

### Show Tags

24 Oct 2007, 14:00
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Function F(x) satisfies F(x) = F(x^2) for all of x. Which must be true?

A. F(4) = F(2) * F(2)
B. F(16) - F(-2) = 0
C. F(-2) + F(4) = 0
D. F(3) = 3* F(3)
E. F(0) = 0

Can someone explain the approach to solving this Q?
VP
Joined: 08 Jun 2005
Posts: 1145
Followers: 7

Kudos [?]: 213 [0], given: 0

### Show Tags

24 Oct 2007, 14:11
You don't need to solve the given function, only to know that F(x) = F(x^2) so:

F(-2) = F(4) = F(16)

F(16) - F(-2) = 0

the answer is (B)

Director
Joined: 11 Jun 2007
Posts: 919
Followers: 1

Kudos [?]: 208 [0], given: 0

Re: PS Functions ^2 [#permalink]

### Show Tags

24 Oct 2007, 14:15
bmwhype2 wrote:
Function F(x) satisfies F(x) = F(x^2) for all of x. Which must be true?

A. F(4) = F(2) * F(2)
B. F(16) - F(-2) = 0
C. F(-2) + F(4) = 0
D. F(3) = 3* F(3)
E. F(0) = 0

Can someone explain the approach to solving this Q?

heh yeah this question was a toughie. i remember struggling with the solution. B is the right answer.

we know that F(x) = F(x^2), so anything in F(x) also going to hold true for F(x^2)

A. F(4) = F(2) * F(2) -> F(2) = F(4) so F(2) * F(2) is actually [F(x)]^2 NOT
F(x^2)

B. F(16) - F(-2) = 0 -> can also rewrite F(16) = F(-2), so since F(x) = F(x^2), then this must be true: F(-2) also equal to F(4)= F(16),

C. F(-2) + F(4) = 0 -> adding them together would not make it true. it would be 2F(x) => F(-2) - F(4) = 0 would be true (same logic as B)

D. F(3) = 3* F(3) -> this is false. the RHS will always be 3 times more LHS or 0 depending on the function of F(x)

E. F(0) = 0 -> F(0) = 0 not necessarily equal to F(0) = F(0)!!! We do not know what F(x) is. For instance, F(x) = x + 1 = F(0) = 0 + 1 = 1 (not 0 in this case)
Re: PS Functions ^2   [#permalink] 24 Oct 2007, 14:15
Display posts from previous: Sort by

# Function F(x) satisfies F(x) = F(x^2) for all of x. Which

 post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.